Elementary School Program Management Bosowa Nature School, Makassar (Educational Management, 2022)
The aims of this study are to 1) describe and analyze the management planning, 2) to describe and analyze the implementation. 3) Describe and analyze the evaluation of the Management 4) Describe and analyze the achievement of the Natural School Primary School Program at the Bosowa Natural School Makassar. Bosowa Nature School implements the Bosowa Nature School curriculum and the Independent Learning Curriculum which are combined and focus on eight things, namely, moral development, leadership, logical thinking, entrepreneurial spirit, Global Diversity, Mutual Cooperation, Critical Morals, Independent. This study uses a qualitative approach, namely research that prioritizes data collection or the reality of the problem based on the disclosure of what has been explored by the respondent. Sampling of data sources is carried out purposively, data collection techniques are triangulation (combined), data analysis is inductive/qualitative, and qualitative research results emphasize meaning rather than generalization. For data collection techniques through observation, documentation and interviews. Methods of data analysis using descriptive methods. The research result information and data in the field about the management (planning, implementation, evaluation and achievement) of the Bosowa Natural School Elementary School program according to the 8 focuses that must be met in Bosowa Natural School of these 8 focuses can be developed into School programs Natural.